SISTEM DETEKTOR ARAH SINYAL RF MENGGUNAKAN ANTENA DOPPLER - Kristiyana, Samuel (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2015)
Two-Way Communication technology uses electromagnetic waves growing very rapidly. Various areas of public life, military and emergency purposes using the radio frequency spectrum, which would be very helpful. This communication system weakness, can not be used to emit a frequency along the same Waku. When this happens as a result of communication will be closed (jammed) for crowded frequency sometimes even no intent to disrupt a lot happening in the field of communication such as radio amateur frequencies. Directional Finder conventional radio has served for many years used to look for the direct nuisance frequency transmitter that has now been inefficient in terms of time and operations. Doppler system applications with Adaptive systems can be used as the basis for the work of Radio Stand Finder to detect the direction of the position of the RF transmitter without direct mobility. Roanoke Doppler antenna designed with a system of switching and amplifier signal reception by the arrangement of square-4 half-wavelength antenna that can determine the direction of the RF signal. Adaptive system can help lock the receiver system information is based on strong towards the greatest signal intensity.